Synthesis of Dicationic Carbazole and 4'-Amino-(3,3'-bipyridine)-4-ol and the Spectral Characteristics of Carbazoles - Wang, K.; Li, T.; Ye, X.M.; Guo, P.; Jia, T. (Asian Journal of Chemistry, 2013)
The dicationic carbazole compound, 3,6-dimethyl-3,6-diazacarbazole diiodide (8) was prepared with 3-bromopyridine as a starting material by a six-step synthesis. The intermediates and target compound were confirmed by IR, NMR and MS. Meanwhile, UV-visible and fluorescent characteristics of 3,6-diazacarbazole (7) and 3,6-dimethyl-3,6-diazacarbazole diiodide (8) were investigated. It was found that fluorescence decay over time of dicationic carbazole existed in low ionic strength and high ionic strength could stabilize the fluorescence of dicationic carbazole.